KEPUTUSAN MEMILIH SEKOLAH DITINJAU DARI ASPEK RELIGIUSITAS, PERSEPSI, DAN MOTIVASI DI SMK NU BAHRUL ULUM GRESIK - Yusuf, Ahmad; widodo, Agus purbo; jondar, aloysius (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze and determine the influence of religiosity, perception, and motivation on the decision to attend SMKNU Bahrul Ulum Gresik. Respondents were parents or guardians of students attending SMKNU Bahrul Ulum Gresik. The study included three independent variables: religiosity, perception, and motivation, and one dependent variable: the decision to attend SMKNU Bahrul Ulum Gresik. The research methodology included instrument design, instrument testing, questionnaire distribution, questionnaire results quantification, descriptive analysis, multiple linear regression analysis, classical assumption testing, and hypothesis testing. Based on the analysis, it can be concluded that religiosity, perception, and motivation have a significant and simultaneous influence on the decision to attend SMKNU Bahrul Ulum Gresik. Religiosity has a positive and significant influence on the decision to attend SMKNU Bahrul Ulum Gresik. Perception has a positive and significant influence on the decision to attend SMKNU Bahrul Ulum Gresik. There is a positive and significant influence of the Motivation variable on the Decision to Choose SMKNU Bahrul Ulum Gresik. This study also yielded an R-square of 0.726, meaning 72.6% of the variation in parents' decisions to choose SMK NU Bahrul Ulum Gresik can be jointly explained by three variables: Religiosity, Perception, and Motivation. The remaining 27.4% is explained by other factors, such as reputation, school accreditation, cost, transportation distance, influence from parents or friends, facilities, job prospects, flagship programs, and others.